Market Power in Water Markets - Erik Ansink; Harold Houba (Tinbergen Institute, 2010)
Water markets with market power are analysed as multi-market Cournot competition in which the river structure constrains access to local markets and limited resources impose capacity constraints. Conditions for uniqueness are identified. Lerner indices are larger under binding resource constraints. The number of cases explodes in the number of local markets. Under quadratic benefit functions and symmetric constant marginal extraction costs, closed-form solutions for selected cases are derived, and numerical implementation through a single optimization program is available. Upstream locations face less competition than downstream. Observed price patterns in the Goulburn-Murray Irrigation District are consistent with the theoretical results.
Keywords: C72; C73; Q25; 330; Water markets; oligopoly; market power; Cournot-Walras equilibrium; Wasserwirtschaft; Marktmacht; Oligopol; Allgemeines Gleichgewicht; Nichtkooperatives Spiel; Dynamisches Spiel; Neusüdwales